Phytochemistry predicts habitat selection by an avian herbivore at multiple spatial scales. Issue 2 (1st February 2013) - Frye, Graham G.; Connelly, John W.; Musil, David D.; Forbey, Jennifer S.
Abstract : Animal habitat selection is a process that functions at multiple, hierarchically structured spatial scales. Thus multi‐scale analyses should be the basis for inferences about factors driving the habitat selection process. Vertebrate herbivores forage selectively on the basis of phytochemistry, but few studies have investigated the influence of selective foraging (i.e., fine‐scale habitat selection) on habitat selection at larger scales. We tested the hypothesis that phytochemistry is integral to the habitat selection process for vertebrate herbivores. We predicted that habitats selected at three spatial scales would be characterized by higher nutrient concentrations and lower concentrations of plant secondary metabolites (PSMs) than unused habitats. We used the Greater Sage‐Grouse ( Centrocercus urophasianus ), an avian herbivore with a seasonally specialized diet of sagebrush, to test our hypothesis. Sage‐Grouse selected a habitat type (black sagebrush, Artemisia nova ) with lower PSM concentrations than the alternative (Wyoming big sagebrush, A. tridentata wyomingensis ). Within black sagebrush habitat, Sage‐Grouse selected patches and individual plants within those patches that were higher in nutrient concentrations and lower in PSM concentrations than those not used. Our results provide the first evidence for multi‐scale habitat selection by an avian herbivore on the basis of phytochemistry, and they suggest that phytochemistry may be a fundamental driver of habitat selection for vertebrate herbivores.